Continuing professional development in the accounting profession: Practices and perceptions from the Asia Pacific region - DE LANGE, Paul (Institutional Knowledge at Singapore Management University, 2015)
Drawing on research in the sociology of professions as a reference point, this study examines the practices and perceptions of professional accountants towards the requirements of IES7 on continuing professional development (CPD). Responses from 1310 accountants in the Asia Pacific region suggest while increasing globalisation has led to more unified standards of professionalism, the perceptions of these standards are not uniform across the region. While there is some consensus that the ongoing development of accounting as part of globalisation, significant differences were identified in perceptions towards CPD offerings between professional accountants in developed economies, compared with emerging economies. Differences in perceptions of CPD offerings were most prevalent in relation to satisfaction with requirements, experience, quality and the appropriateness of the level of CPD. The findings suggest that global uniform CPD offerings fail to meet the aspirations of accountants in emerging economies, highlighting the need for increasingly diverse forms of CPD activities.